Studi cross-sectional tentang pengetahuan dan sikap pengunjung puskesmas Denpasar Utara II terkait dengan antibiotika - Made Cindy Widya Murthi; I Gusti Ayu Artini (E-Jurnal Medika Udayana, 2018)
Antimicrobial resistance has increased drastically in both developed and developing countries. According to the CDC (Centers for Disease Control and Prevention), outpatient antibiotic overuse in the USA was a particular problem in the Southeast. In India, uropathogenic Eschericia coli (UPEC) has showed their resistance to ampicillin, co-trimoxazole, and ciprofloxacin for UPEC were 85, 74, and 72% respectively. Study that conducted in two cities in Indonesia, Semarang and Surabaya revealed 8% of Eschericia coli showed their resistance to ciprofloxacin. A study revealed that knowledge and beliefs are social cognitive factors that influence health-related behavior, such as the behavior of using antibiotics.The purpose of this study was to describe the visitor’s knowledge and beliefs regarding the use of antibiotics in Puskesmas Denpasar Utara II working area. This study was a cross-sectional study and a consecutive sampling technique was applied (N = 49). Data were collected using a pre-tested questionnaire and analyzed using descriptive statistics. The results showed 22.4% of respondents were at the poor level, 40.8% had moderate level of knowledge, 36.7% had adequate knowledge, and 69.4% respondents had appropriate beliefs while the rest (30.6%) had inappropriate beliefs about the use of antibiotic. In conclusion misconceptions regarding antibiotic use exist among people in this study. Therefore, improving appropriate knowledge regarding antibiotic is required. Keywords: knowledge, beliefs, antibiotics, antibiotic resistance